PERENCANAAN STRUKTUR BAJA PADA BANGUNAN KANTOR SEWA TUJUH LANTAI DI PONTIANAK - Suganda, Agus; Samsurizal, Eddy; Sutandar, Erwin (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
As the provincial capital of Pontianak to become the main business events destinations and is a barometer for the development of other areas in West Kalimantan. Business development in Pontianak will have an impact on increasing office space requirements, but it raises new problems, namely the limitation of the availability of land. To overcome this problem one alternative solution is the construction of a multi-story building. With a storied building can increase the capacity of office spaces, so the need for Office space can be fulfilled. In this final Task, carried out the planning of the steel structure SPRMB (Bearers of ordinary Moment Frame System) includes the planning of primary and secondary structure of the Foundation based on SNI 1729:2015, SNI 1726:2012, SNI 2847:2013, SNI: 1727:2013 and others. The analysis is done by software ETABS 2016 version 16.2. The results of the calculation of the results obtained, namely: roof and floor plates thick 10 cm, the typical parent WF beam dimensions 450,200 column dimension, King Cross 600,300, H-beam and H-beam 400,400 300,300 in the elevator. The connection to the main structure is planned as a high-quality connections with bolts fub 625 MPa. Planning the Foundation using concrete powerboats square 20 x 20 size with a depth of 24 m. Key words: SPRMB (Bearers of ordinary Moment Frame System), steel structures, Planning.